Medical Cannabis Induced Acute Pancreatitis and Hyperemesis Syndrome in a Patient with Complex Regional Pain Syndrome - Cheryl Hutflesz; Vikas Parihar (Taylor & Francis Group, 2019)
Introduction: Medical cannabis is being utilized for intractable pain that is not well managed through conventional means. There are reports of cannabis induced hyperemesis syndrome and acute pancreatitis amongst recreational users inhaling cannabis, but not amongst medical users consuming cannabis orally. Patient Case: A 33-year old male with complex regional pain syndrome initiated 1 g of medical cannabis per day consisting of CBD (25 mg/mL) and tetrahydrocannabinol (<2 mg/mL). He transitioned to a balanced 50:50 CBD to THC product 12.5 mg/mL of each every six hours. He achieved good pain and anxiety relief but developed gastrointestinal cramping, bloating, intermittent nausea and vomiting which he managed with homeopathic remedies. He added THC only at bedtime and symptoms exacerbated over 3 months. He experienced worsening abdominal pain, nausea, projectile vomiting and weight loss. He was found to have epigastric and right and left upper quadrant abdominal tenderness as well as elevated lipase >300. Abdominal ultrasound and CT abdomen with contrast were negative. Serial lipase levels rose to >800. He stopped all cannabis products. Oral Haldol 0.5mg QID was initiated for hyperemesis after ondansetron failure. After 1 week CBD dominant oil was reintroduced at 1ml (25mg) QID for CRPS with no worsening of GI symptoms. After 2.5 weeks off THC hyperemesis dramatically improved, weight loss stabilized and lipase returned to baseline. Conclusion: Chronic oral administration of medical cannabis containing tetrahydrocannabinol resulted in acute pancreatitis and hyperemesis similar to individuals inhaling recreational cannabis. Patients and healthcare providers should be counselled on the rare but serious complications of medical cannabis induced pancreatitis.